The Effect of the Visualization Method in Increasing the Students’ Vocabulary in Grade 2nd At Smp Negeri 1 Gilireng - Anita, Siti; Syam, Ummi Khaerati; Maharida (FKIP Unismuh Makassar, 2025)
This study aims to increase the vocabulary of students at UPT SMP Negeri 1 Gilireng with the visualization method with pictures as teaching materials. The researcher used a pre-experimental study where the data were obtained from students’ vocabulary tests. The population in this study were students of class VIII.A UPT SMP Negeri 1 Gilireng in the 2022/2023 academic year. Based on the result of the study indicated that the use of visualization methods with pictures is very effective in improving the performance of students' vocabulary skills. This can be seen from the differences in student achievement in the pre-test and post-test. The student's score on the pre-test was 34.25 and the post-test was 86.25. This shows that the average value of the Pte-test and post-test increased by 52 points. Data from the instrument also shows that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The findings from the Scientific Approach are good.